Genetic Characterisation of Colistin Resistant Klebsiella pneumoniae Clinical Isolates From North India - Singh, Sanjay; Pathak, Ashutosh; Rahman, Mohibur; Singh, Avinash; Nag, Soumyabrata; Sahu, Chinmoy; Prasad, Kashi Nath (Frontiers in Cellular and Infection Microbiology, 2021)
Background Increasing use of colistin has led to the world-wide emergence of mobile colistin resistant gene (mcr). The present study aimed to identify and characterise mcr and other drug-resistant genes in colistin resistant Klebsiella pneumoniae clinical isolates. Methods Twenty-two colistin resistant K. pneumoniae were analysed for mcr and other drug-resistant genes, efflux pumps, and virulence genes, and for their biofilm forming ability. Pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST) were performed for all mcr-1 positive isolates. S1-PFGE and Southern hybridisation were performed for localisation of mcr-1 and blaNDM. Results Nineteen colistin resistant K. pneumoniae harboured mcr-1 and 3 had mgrB disruption. All isolates harboured blaOXA-48-type and ESBL genes; eight strains (five with mcr-1 and three with mgrB disruption) co-harboured blaNDM. Efflux pumps genes AcrAB and mdtK were detected in all 22 and tol-C in 21 isolates. Virulence-related genes entB and irp-1 were detected in all 22, mrkD in 20, and fimH-1 in 18 isolates; 11 isolates were strong biofilm producers. PFGE clustered mcr-1 positive isolates into eight groups based on ≥90% similarity; MLST revealed diverse sequence types, predominant being ST-15 (n = 4) and ST-16 (n = 4). Both mcr-1 and blaNDM were localised on plasmid and chromosome; mcr-1 was present on IncFII type and blaNDM on IncFIB and IncA/C type plasmids. Conclusions Colistin resistance in K. pneumoniae was predominantly mediated by mcr-1. Co-existence of colistin, carbapenem, and other drug-resistant genes along with efflux pumps indicates towards enormous genomic plasticity in K. pneumoniae with ability to emerge as super-spreader of drug-resistance.